Rare bird documentation form for Northern Goshawk at Waterloo, 1984 - Moore, Francis L.et al (1984)
Rare bird documentation form for a Northern Goshawk at Waterloo in Black Hawk County, IA on October 3, 1984. Epson - sheet feed